Body mass index and survival after diagnosis of invasive breast cancer: a study based on the Japanese National Clinical Database—Breast Cancer Registry. (29th February 2016) - Kawai, Masaaki; Tomotaki, Ai; Miyata, Hiroaki; Iwamoto, Takayuki; Niikura, Naoki; Anan, Keisei; Hayashi, Naoki; Aogi, Kenjiro; Ishida, Takanori; Masuoka, Hideji; Iijima, Kotaro; Masuda, Shinobu; et al.
Abstract: Few studies have reported the association between body mass index (BMI) and outcome among Asian breast cancer patients. We analyzed data for 20, 090 female invasive breast cancer patients who had been followed‐up for a median period of 6.7 years entered in the National Clinical Database–Breast Cancer Registry between 2004 and 2006. We used mainly the WHO criteria for BMI (kg/m 2 ) categories; <18.5 (underweight), ≥18.5–<21.8 (reference), ≥21.8–<25, ≥25–<30 (overweight), and ≥30 (obese). We divided normal weight patients into two subgroups because this category includes many patients compared to others. The timing of BMI measurement was not specified. The Cox proportional hazards model and cubic spline regression were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs). Smoking, alcohol, and physical activity were not controlled. A total of 1418 all‐cause, 937 breast cancer–specific deaths, and 2433 recurrences were observed. Obesity was associated with an increased risk of all‐cause (HR: 1.46; 95% CI: 1.16–1.83) and breast cancer–specific death (HR: 1.47; 95% CI: 1.11–1.93) for all patients, and with all‐cause (HR: 1.47; 95% CI: 1.13–1.92) and breast cancer–specific death (HR: 1.58; 95% CI: 1.13–2.20) for postmenopausal patients. Being underweight was associated with an increased risk of all‐cause death for all (HR: 1.41; 95% CI: 1.16–1.71) and for postmenopausal patients (HR: 1.45; 95% CI: 1.15–1.84). With regard to subtype and menopausal status, obesity was associated with an increased risk of breast cancer–specific death for all cases of luminal B tumor (HR: 2.59; 95% CI: 1.51–4.43; Pheterogeneity of Luminal B vs. Triple negative = 0.016) and for postmenopausal patients with luminal B tumor (HR: 3.24; 95% CI: 1.71–6.17). Being obese or underweight is associated with a higher risk of death among female breast cancer patients in Japan. Abstract : Few studies have reported the association between body mass index and outcome among Asian breast cancer patients. We analyzed data for 20, 090 female invasive breast cancer patients who had been followed up for a median period of 6.7 years (119, 873.4 person years) entered in the National Clinical Database–Breast Cancer Registry between 2004 and 2006. The timing of body mass index (BMI) measurement was not specified. Being obese or underweight is associated with a higher risk of death among female breast cancer patients in Japan.